(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of this article is to provide research-based techniques successful in improving the writing skills of EFL students. The findings suggest that through the use of technology, pre-taught vocabulary, various teacher influences and the implementation of positive diverse literacy practices, this goal can be attained.